Effects of supplemental trace minerals and prevaccination on stressed calves - Lindell, S.A.; Brandt, Robert T., Jr.; Stokka, Gerald L.; Gramlich, S.M.; Milton, C.T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to evaluate the effect of high dietary levels of trace minerals on performance and health of stressed calves. In trial 1, 221 Brahman crossbred steers (674 l b, 1/8 to 1/4 Brahman) were used to evaluate the effect of copper (Cu) and zinc (Zn) supplementation on performance and immune response. The steers were shipped from northern Texas to the KSU Beef Research Un it with an 18-hour transit time. Receiving diets were formulated to contain 1) NRC-recommended levels of Cu and Zn or 2) 4 times re commended levels. In trial 2, 112 Angus cross steers (518 lb) were used to evaluate effects of the same trace mineral supplementation and preweaning vaccination on performance and immune response. Half of the steers were vaccinated (modified live IBR, BVD, P I , 3 BRSV) 14 days prior to weaning, and all were vaccinated at weaning (day 0). No differences occurred in dry matter intake, daily gain, serum Zn and Cu , or IBR antibody titer as a result of trace mineral level in either study. Prevaccination had no effect on performance or health of weaned calves. However, IBR antibody titers at weaning (day 0) were higher (P<.001) for prevaccinated vs non-prevaccinated calves. We concluded that either the level of stress imposed in the two trials was not great enough to cause acute trace mineral deficiencies, or that NRC-recommended levels are adequate for stressed as well as non-stressed animals. Prevaccination with a modified live vaccine resulted in an elevated antibody titer response but no improvement in health of newly weaned calves.
Keywords: Beef; Bovine respiratory disease; IBR; Zinc; Copper; Morbidity